Evaluating Initial Empiric Therapy for Neutropenic Fever in Vancomycin-Resistant Enterococcus-Colonized Patients. (21st September 2021) - Snyder, Matthew; Pasikhova, Yanina; Baluch, Aliyah
Objectives: Vancomycin-resistant enterococcus infections impact mortality in oncology patients. Given the low rate of vancomycin-resistant enterococcus bacteremia, low virulence of vancomycin-resistant enterococcus, and advent of rapid diagnostic systems, vancomycin-resistant enterococcus-directed empiric therapy in vancomycin-resistant enterococcus-colonized patients with neutropenic fever may be unnecessary, promoting increased antimicrobial resistance, drug-related toxicity, and cost. Methods: Vancomycin-resistant enterococcus-colonized adults admitted for hematopoietic stem cell transplantation or induction therapy for acute leukemia/myeloid sarcoma with neutropenic fever were stratified by vancomycin-resistant enterococcus bacteremia development and empiric vancomycin-resistant enterococcus-directed antimicrobial strategy for first neutropenic fever (Empiric Therapy vs. non-Empiric Therapy). Primary endpoints included vancomycin-resistant enterococcus-related, in-hospital, and 100-day mortality rates. Secondary outcomes included vancomycin-resistant enterococcus bacteremia incidence for first neutropenic fever and the entire hospitalization, length of stay, Clostridioides difficile infection rate, and duration and cost of vancomycin-resistant enterococcus-directed therapy. Results: During first neutropenic fever, 3 of 70 eligible patients (4%) developed vancomycin-resistant enterococcus bacteremia. Although all 3 (100%) were non-Empiric Therapy, no mortality (0%) occurred. Of 67 patients not developing vancomycin-resistant enterococcus bacteremia, 42 (63%) received Empiric Therapy and 25 (37%) non-Empiric Therapy. Empiric Therapy had significantly greater median duration (3 days vs. 0 days; P<.001) and cost ($1604 vs. $0; P<.001) of vancomycin-resistant enterococcus-directed therapy but demonstrated no significant differences in clinical outcomes. Conclusion: Available data suggest Empiric Therapy may offer no clinical benefit to this population, regardless of whether vancomycin-resistant enterococcus is identified in blood culture or no pathogen is found. Such an approach may only expose the majority of patients to unnecessary vancomycin-resistant enterococcus-directed therapy and drug-related toxicities while increasing institutional drug and monitoring costs. Even in the few patients developing vancomycin-resistant enterococcus bacteremia, waiting until the organism is identified in culture to start directed therapy likely makes no difference in mortality. This lack of benefit warrants consideration to potentially omit empiric vancomycin-resistant enterococcus-directed therapy in first neutropenic fever in many of these patients.